Bone Marrow GvHD after Allogeneic Hematopoietic Stem Cell Transplantation - Szyska, Martin; Na, Il-Kang (Frontiers in Immunology, 2016)
The bone marrow is the origin of all hematopoietic lineages, as well as an important homing site for memory cells of the adaptive immune system. It has recently emerged as a graft-versus-host-disease (GvHD) target organ after allogeneic stem cell transplantation (alloHSCT), marked by depletion of both hematopoietic progenitors and niche-forming cells. Serious effects on the restoration of hematopoietic function and immunological memory are common especially in patients after myeloablative conditioning therapy. Cytopenia and durable immunodeficiency caused by the depletion of hematopoietic progenitors and destruction of bone marrow niches negatively influence the outcome of alloHSCT. The complex balance between immunosuppressive and cell-depleting treatments, GvHD and immune reconstitution as well as the desirable graft-versus-tumor (GvT) effect remains a great challenge for clinicians.